2020
DOI: 10.1155/2020/3560310
|View full text |Cite
|
Sign up to set email alerts
|

Species Composition, Phenotypic and Genotypic Resistance Levels in Major Malaria Vectors in Teso North and Teso South Subcounties in Busia County, Western Kenya

Abstract: Introduction. Knockdown resistance (kdr) is strongly linked to pyrethroid insecticide resistance in Anopheles gambiae in Africa, which may have vital significance to the current increased use of pyrethroid-treated bed net programmes. The study is aimed at determining species composition, levels of insecticide resistance, and knockdown patterns in Anopheles gambiae sensu lato in areas with and areas without insecticide resistance in Teso North and Teso South subcounties, Western Kenya. Materials and Methods. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…Human blood index was the proportion of blood-fed mosquitoes that fed on humans calculated as the number of samples positive for human blood divided by the total number of mosquitoes tested. More information on materials and methods used in this study is found in my linked paper [32] published @ "https:// www.hindawi.com/journals/jpr/2020/3560310/";…”
Section: Detection Of Blood Meal Sources Using Polymerase Chainmentioning
confidence: 99%
See 1 more Smart Citation
“…Human blood index was the proportion of blood-fed mosquitoes that fed on humans calculated as the number of samples positive for human blood divided by the total number of mosquitoes tested. More information on materials and methods used in this study is found in my linked paper [32] published @ "https:// www.hindawi.com/journals/jpr/2020/3560310/";…”
Section: Detection Of Blood Meal Sources Using Polymerase Chainmentioning
confidence: 99%
“…Genotypically, homozygous SS genotype carrying mosquitoes were resistant to insecticides while the homozygous LL carrying genotypes were susceptible. More results on species composition and insecticide resistance are explored in Githinji et al, 2019 [32].…”
Section: Phenotypic and Genotypic Resistance Levels For Allmentioning
confidence: 99%
“…and An . funestus [ 21 ] that exhibit endophilic and endophagic behaviors [ 62 , 63 ]. Spending more time indoors thus increases the risk of infection.…”
Section: Discussionmentioning
confidence: 99%
“…The main mosquito vectors in PLOS GLOBAL PUBLIC HEALTH this region are Anopheles gambiae s.s. and An. funestus [21] that exhibit endophilic and endophagic behaviors [62,63]. Spending more time indoors thus increases the risk of infection.…”
Section: Discussionmentioning
confidence: 99%
“…The main mosquito vectors in this region are Anopheles gambiae s.s. and An. funestus [21] that exhibit endophilic and endophagic behaviors [56,57]. Spending more time indoors thus increases the risk of infection.…”
Section: Discussionmentioning
confidence: 99%